DETERMINAN PERSONAL HYGIENE DAN PENGETAHUAN NUTRISI: STUDI KASUS PADA ANAK KELUARGA PRA-SEJAHTERA Di DAERAH PESISIR AMPENAN KOTA MATARAM - Chairun Nasirin (Jurnal PRIMA, 2017)
This Study highlight the determinant of the personal hygiene and the parents knowledge regarding nutrients in relation to children’s health as the behavior of family taking care of their children. For this purpose, researcher used the adapted behavior that focuses on changes of knowledge, attitudes, beliefs and subjective norms in the study population as parts of health management in the low-income family and coastal community on the research site. The most of young mothers generally have poor knowledge about personal hygiene and nutrition. Therefore educational nutrition will greatly affected to the personal hygiene of the children that intervention through this study to change the cultural beliefs practice for better health in the community. Methodology: The qualitative research study was design to use a case study of a determinant of the personal hygiene and nutrients. Methodology refers to the whole procedures to describing, explaining and predicting cases. The setting of this research located in the coastal area of Ampenan, the city of Mataram. Findings: Most of parents in the coastal community have knowledge the impacts of personal hygiene providing children with additional nutrients.